Lecturer At Ease Cycling To Campus - The Star, Maybelline Yeo & Meera Devi Daran (2008)
Cycling to work may seem like an uphill task for most people but not Universiti Putra Malaysia (UPM) Dr. Nor Rasidah Hashim.